Dielectric resonator antenna with reconfigurable polarization states. Issue 7 (9th April 2021) - Iqbal, Amjad; Waly, Mohamed I.; Smida, Amor; Mallat, Nazih K.
Abstract: This study presents a simple and low‐profile cylindrical dielectric resonator antenna (CDRA) for the fifth‐generation (5G) band (3.5 GHz) with switchable polarization. The antenna can operate with linear or circular polarization (right‐handed circular polarization [RHCP] or left‐handed circular polarization [LHCP]) by changing the states of the PIN diodes below the CDRA, while keeping the same operating frequencies. The antenna operates at three modes (Mode 1, Mode 2, and Mode 3). It exhibits linear polarization in Mode 1, RHCP in Mode 2, and LHCP in Mode 3. The 10‐dB bandwidths of 750 MHz (3.1–3.85 GHz), 950 MHz (3.03–3.98 GHz), and 960 MHz (3.03–3.99 GHz) are noted for Mode 1, Mode 2, and Mode 3, respectively. The 3‐dB axial ratio bandwidth of 22.2% (3.09–3.86 GHz) and 21.4% (3.08–3.82 GHz) is achieved for Mode 2 and Mode 3, respectively. The reported antenna has high gain ( >5.25 dBi for all operating modes) and high radiation efficiency ( >79.8% for all operating modes). The proposed antenna is suitable for use in polarization diversity applications.